Basics of Digital Microscopy. Issue 1 (18th January 2018) - Wallace, Callen T.; Jessup, Morgan; Bernas, Tytus; Peña, Karina A.; Calderon, Michael J.; Loughran, Patricia A.
Abstract: Modern digital microscopy combines the equipment of classical light microscopy with a computerized imaging system. The technique comprises image formation by optics, image registration by a camera, and saving of image data in a computer file. This chapter describes limitations that are particular to each of these processes, including optical resolution, efficiency of image registration, characteristics of image file formats, and data management. Further suggestions are given which serve, in turn, to help construct a set of guidelines aimed at optimization of digital microscopic imaging. © 2018 by John Wiley & Sons, Inc.